Covid-19 and air transport in Iraq, implications and treatments : A Study in Transport Geography) - Al – Jubouri, Ass Prof.Dr. Shurooq Naim Jassim (Thi Qar Arts Journal, 2022)
The research aims to study the impact of Covid-19 on air transport in Iraq by identifying the air transport movement during the years 2019 and 2020, and what is the impact of the spread of the virus on the number of flights and the movement of passengers at Iraqi airports, and what are the most important treatments used to limit the spread of its spread. As air transport has become a new challenge, the worst of its kind, due to the outbreak of the Covid-19 virus, as this pandemic imposed a new reality on its movement. The closure to limit the spread of the virus, as the air transport movement for regular flights was stopped at Iraqi airports, starting from (March 17, 2020) until (July 23, 2020).Despite the profound negative repercussions of the spread of the virus on air transport, it plays an important role, as the General Company for Iraqi Airways continued its cross-border flights to ensure the flow of supplies of goods, supplies and medical devices necessary to combat the epidemic, as well as some flights to transport stranded passengers for the purpose of evacuating citizens and their return to Iraq. At a later stage, the Iraqi state began formulating new measures to resume travel through several policies, including: redesigning aircraft and airports to adapt to the post-Corona changes..